Review on Molecular Targeting, Pharmacological Action, and Advanced Biopharmaceutical Aspects for the Management of Alzheimer’s Disease - Gupta, Ram Ajay; Rajni; Shah, Kamal; Dewangan, Hitesh Kumar (Current Pharmaceutical Design, 2025)
Alzheimer’s disease (AD) is an ongoing progressive neurodegenerative disorder that predominantly affects elderly individuals. A systematic literature search was conducted using electronic databases such as PubMed, Scopus, Web of Science, and Google Scholar. Peer-reviewed articles, clinical trial reports, and experimental studies published in English within the last 15 years were considered. The keywords used for the search included “Alzheimer’s disease,” “amyloid-beta,” “tau protein,” “neuroinflammation,” “immunotherapy,” “drug repurposing,” and “experimental treatment strategies.” It is the most common form of dementia, ultimately leading to death in advanced stages. Recent advances in AD have featured the expected role of anti-amyloid, anti-tau, and anti-inflammatory therapies. Nonetheless, these treatments are still in various stages of preclinical and clinical trials. Moreover, drug repurposing is another promising avenue to identify effective therapeutic alternatives for Alzheimer's disease. This review highlights the underlying pathophysiological mechanisms of AD along with the limits of existing treatments. It also includes two methodologies, specifically; active immunotherapy and passive immunotherapy. Active immunotherapy tactics include the administration of antigens to stimulate antibody production. Additionally, this study discusses several experimental drugs and novel pharmaceutical approaches for AD.
Keywords: Clinical trial